(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes effective methods of motivating students through the use of software platforms in the educational process. The article demonstrates how motivation increases students’ engagement and active participation in learning. In particular, the use of the "happy call" method in education and its role in encouraging student success is described in detail. This method not only allows students to present their achievements but also provides support by connecting with their parents. The article also discusses the importance of software platforms in tracking and monitoring students’ development.